Efektivitas Kebijakan Perizinan Berbasis Online Single Submission (Oss) Dalam Mendukung Paperless Di Dpmptsp Kota Tanjungpinang - Nathasia Angelina Saragi; Nazaki .; Ella Afnira (CV. ITTC INDONESIA, 2026)
The Tanjungpinang City DPMPTSP has implemented an Online Single Submission (OSS)-based licensing policy as an effort to support paperless licensing services. This study aims to determine the effectiveness of this policy. The problem in this study is the continued use of physical documents despite the OSS implementation, thus the paperless concept has not yet been fully realized. This study uses a descriptive method with a qualitative approach. Data were collected through interviews and documentation. The results show that the OSS has transformed the licensing service process into a digital system, but it has not yet fully supported paperlessness because the public still requires assistance from officers and physical documents. The OSS system has reached the public and business actors, but its utilization is not evenly distributed due to the limited ability of the public to use the system independently. The level of public satisfaction is also not fully optimal. In terms of input, the DPMPTSP has adequate human resources and facilities and infrastructure, but the service output is not optimal because the public still needs assistance. Overall, the Online Single Submission (OSS)-based licensing policy in supporting paperless at the Tanjungpinang City Department of Public Works and Public Housing (DPMPTSP) has not been implemented effectively.